The Baby Friendly Hospital Initiative and breast feeding rates in Scotland. Issue 2 (21st February 2005) - Broadfoot, M; Britten, J; Tappin, D M; MacKenzie, J M
Abstract : Objective: To examine the effect of the Baby Friendly Hospital Initiative on breast feeding rates in Scotland. Design: Observational study using an annual survey of progress towards the WHO/UNICEF Baby Friendly Hospital Initiative and routinely collected breast feeding rates gathered on the Guthrie Inborn Errors Screening card at 7 days of postnatal age. Setting: Scotland, UK, population 5.1 million, with about 53 000 births a year. Participants: All 33 maternity units with over 50 births per annum and 464 246 infants born in Scotland between 1995 and 2002. Main outcome measures: Baby Friendly status of each maternity unit at the time of an infant's birth: certificate of commitment, UK standard award, and breast feeding at 7 days postnatal age. Results: Babies born in a hospital with the UK Baby Friendly Hospital Initiative standard award were 28% (p < 0.001) more likely to be exclusively breast fed at 7 days of postnatal age than those born in other maternity units after adjustment for mother's age, deprivation, hospital size, and year of birth. From 1995, breast feeding rates had increased significantly faster in hospitals with Baby Friendly status by 2002: 11.39% (95% confidence interval 10.35 to 12.43) v 7.97% (95% confidence interval 7.21 to 8.73). Conclusion: Being born in a hospital that held the award increased the chance of being breast fed. All maternity units should be encouraged to undertake the significant strategic and practical changes required to achieve UK Baby Friendly Hospital Initiative standard status.